Infectious agents and inflammation in donated hearts and dilated cardiomyopathies related to cardiovascular diseases, Chagas' heart disease, primary and secondary dilated cardiomyopathies. (15th January 2015) - Mangini, Sandrigo; Higuchi, Maria de Lourdes; Kawakami, Joyce Tiyeko; Reis, Marcia Martins; Ikegami, Renata Nishiyama; Palomino, Suely Aparecida Pinheiro; Pomerantzeff, Pablo Maria Alberto; Fiorelli, Alfredo Inácio; Marcondes-Braga, Fabiana Goulart; Bacal, Fernando; Ferreira, Sílvia Moreira Ayub; Issa, Victor Sarli; et al.
Abstract: Background: Clinical and experimental conflicting data have questioned the relationship between infectious agents, inflammation and dilated cardiomyopathy (DCM). Objectives: The aim of this study was to determine the frequency of infectious agents and inflammation in endomyocardial biopsy (EMB) specimens from patients with idiopathic DCM, explanted hearts from different etiologies, including Chagas' disease, compared to donated hearts. Methods: From 2008 to 2011, myocardial samples from 29 heart donors and 55 patients with DCMs from different etiologies were studied (32 idiopathic, 9 chagasic, 6 ischemic and 8 other specific etiologies). Inflammation was investigated by immunohistochemistry and infectious agents by immunohistochemistry, molecular biology, in situ hybridization and electron microscopy. Results: There were no differences regarding the presence of macrophages, expression of HLA class II and ICAM-I in donors and DCM. Inflammation in Chagas' disease was predominant. By immunohistochemistry, in donors, there was a higher expression of antigens of enterovirus and Borrelia, hepatitis B and C in DCMs. By molecular biology, in all groups, the positivity was elevated to microorganisms, including co-infections, with a higher positivity to adenovirus and HHV6 in donors towards DCMs. This study was the first to demonstrate the presence of virus in the heart tissue of chagasic DCM. Conclusions: The presence of inflammation and infectious agents is frequent in donated hearts, in the myocardium of patients with idiopathic DCM, myocardial dysfunction related to cardiovascular diseases, and primary and secondary cardiomyopathies, including Chagas' disease. The role of co-infection in Chagas' heart disease physiopathology deserves to be investigated in future studies.